Development and experimental validation of a PEM fuel cell 2D-model to study heterogeneities effects along large-area cell surface. (24th August 2015) - Robin, Christophe; Gerard, Mathias; d'Arbigny, Julien; Schott, Pascal; Jabbour, Lara; Bultel, Yann
Abstract In this work, a PEM fuel cell 2D + 1D model has been developed to investigate the heterogeneities existing at the surface of a cell. A study on the effects of the operating conditions is carried out. The fuel cell behavior is monitored through its interactions with local conditions thanks to the model. A GDL structuring and its effect on local conditions are also analyzed. The model has been confronted with stack test results in several operating conditions with an in-situ device. The comparison in three very distinctive humidity regimes (dry, mid-hydrated, fully hydrated) between the model and the measures for two local conditions (current density and temperature distributions) has enabled to validate the model and its approach. Other local conditions computed by the model but hardly reachable in real life have then been examined to better understand the cell's electrochemical behavior. In particular, temperature distribution measurements show that three hot spots exist at the cell surface, being located where the cooling fluid reaches a low velocity for a given bipolar plates' design. The current density distribution is the result of the interactions between the temperature, relative humidity and molar fractions distributions along the cell surface. The in-plane GDL structuring shows an improvement of current density homogeneity in dry conditions.